The Higher Water Absorption Capacity of Small Root System Improved the Yield and Water Use Efficiency of Maize - Minfei Yan; Li Zhang; Yuanyuan Ren; Tingting Zhang; Shaowei Zhang; Hongbing Li; Yinglong Chen; Suiqi Zhang (Plants, 2022)
The root system in plants absorbs water and minerals. However, the relationship among root size, yield, and water use efficiency (WUE) is controversial. Two pot experiments were conducted to explore these relationships by using two maize varieties with contrasting root sizes and reducing the root–shoot ratio (R/S) through root pruning to eliminate genotypic effects. Maize plants were grown in an open rainout shelter under both water-sufficient and deficient conditions. Yield-related parameters, root hydraulic conductivity (Lpr), and WUE were determined. The results showed that the small root variety (XY) has a higher yield and WUE compared to large root variety (QL) under both soil moisture conditions, likely related to the higher Lpr of XY. XY also had a higher leaf water potential than QL under drought stress, indicating that small root system could provide enough water to the shoot. Further pot experiment showed that both small and large root pruning on QL (cut off about 1/5 roots, RP1; and cut off about 1/3 roots, RP2, respectively) improved WUE and Lpr, and the RP1 yield increased by 12.9% compared to the control under well-watered conditions. Root pruning decreased transpiration and increased photosynthesis. Thus, this study reveals that it is possible to increase water absorption, yield, and WUE by reducing R/S in modern maize varieties, which may be important for the future breeding of new cultivars suitable for arid regions.